Sand country, Levi Ranges, Bagot, Pituri, Northern Territory, 1947 - Groom, Arthur, 1904-1953. (1947)
Men travelling by camels.
Title devised by cataloguer based on inscriptions below the photograph.
Inscriptions: "Sand country Levi, Bagot, Piutri".
Part of collection: Album of photographs of Central Australia.
Condition: Good
Also available online
Keywords: Groom, Arthur, -- 1904-1953 -- Journeys -- Northern Territory -- Photographs; Levi Range (N.T.) -- Photographs